Early History of Oral Contraceptive Pill in Finland: The Diffusion of the New Contraceptive and Fertility Patterns - Aura Pasila (Finnish Yearbook of Population Research, 2011)
The 1960s is often characterized as a decade of outstanding social and demographic changes in Western societies. The introduction of the contraceptive pill is assumed to have contributed to these changes. Yet the social as well as the demographic significance of the pill is ambiguous. This article has two aims: 1) to describe the early history of the pill in Finland in the 1960s and in the early 1970s and 2) to explore relationships between fertility and the pill. Surveys, pharmaceutical market data, and estimations are used to depict the diffusion of the pill. Based on calculated user percentages, the pill was adopted neither instantly nor extremely widely in Finland during the period under study. The results show that the diffusion coincided with fertility decline and other changes in fertility patterns. However, a causal connection of any kind cannot be established due to a lack of sufficient data.